Scientific heritage of V. M. Nadelyayev and modern Tuvinology - Bicheldey, Kaadyr-ool A. (The New Research of Tuva, 2012)
This is a greeting speech of Tuvan Minister for Education and Science on May 20, 2012 at the opening of the International Science and Practice Conference devoted to 100th anniversary of "Peoples Academic” Vladimir Mikhaylovich Nadeyayev (Kyzyl).
Keywords: conference-2012; speech; V. M. Nadelyayev; jubilee; greeting; Tuvinolgy; philology; Turkology